Development of a Martian in-situ hybrid rocket motor - Babazadeh, Iman Andrew, author; Marchese, Anthony, advisor; Mizia, John, advisor; Bareither, Christopher, committee member (Colorado State University. Libraries, 2020)
One of the chief obstacles that has prevented a human mission to Mars is the excessive amount of mass that must be launched into low earth orbit to assemble the Mars-bound spacecraft. Since propellants alone account for 75% of the total mass requirements, a new concept has been proposed for both manned missions and unmanned robotic sample return missions, which relies on In-Situ Resource Utilization wherein propellants for the return trip to Earth are manufactured from raw materials available on Mars. This research focused on the development and testing of a unique propulsion system that could enable in-situ use of the Martian atmosphere as an oxidizer source and Martian soil as a fuel source for the return journey back to Earth for manned and unmanned vehicles. The propulsion system employs carbon dioxide as an oxidizer and metals as the fuel component. The need to understand and test this concept is significant as there is currently little experimental knowledge on the performance of carbon dioxide oxidizer and metallic fuels in rocket engines. Aluminum and magnesium fuels are the leading choice for burning with carbon dioxide as they can liberate the contained oxygen for rapid combustion to occur. Magnesium is favorable for its ignitability characteristics, whereas aluminum has a higher energy density but is more difficult to ignite due to the formation of its oxide layer. In the research conducted for this thesis, aluminum and magnesium particles were both considered to determine an optimal system that could be used to model an actual Mars propulsion system. The project entailed a myriad of combustion tests based on a conventional hybrid rocket motor in which the metallic fuel particles were encased in a polymer matrix binder and oxidized through a liquid oxidizer. The hybrid rocket motor configuration is not only amenable for the Mars environment because of ease of storage, but also afforded great adaptability safety for the experimental studies described here because of the simplicity of refueling procedures and because the fuel component itself aids in keeping the combustion chamber wall cool, thereby eliminating the need for an active cooling system. Through initial testing, it was observed that adding an additional oxidizer aided in the combustion of carbon dioxide with high percentage metal fuel grains. Specifically, the results of this study suggest that using nitrous oxide as a complementary oxidizer was beneficial in attaining sustained combustion. However, it was also found that miscibility and mixing issues between the carbon dioxide and nitrous oxide oxidizers led to induced combustion instability during the hybrid test fires that had a 50% carbon dioxide and 50% nitrous oxide mixture ratio.